The translation process between Huichol and Spanish - Iturrioz Leza, José Luis; Ramírez de la Cruz, Julio (Estudios de Traducción, 2012)
This paper is based on our own experience in translating technical texts belonging to the fields of linguistics, law and medicine from Spanish to Huichol, a Mexican Uto-aztecan language which can be characterized as polysynthetic, centralizing, verb centered and highly explicit. We focus on the analysis of several drafts documenting the process of the translation of the Gramática Didáctica del Huichol. Translation competence involves grammatical and lexical competence, as well as textual, pragmatic and cultural competence.
Keywords: translation; pragmatic competence; text competence; cultural competence; typological adecuacy.